Perbedaan Pola Peningkatan Suhu Bahan Biologis dan Non-Biologis yang Dipapar Sinar Far-Infrared - Soleh, Miftahu; Sujuti, Hidayat; Widjajanto, Edi (Fakultas Kedokteran Universitas Brawijaya, 2009)
Low power of Far-Infrared Rays (FIR) emitted by artificial radiators have been used for many diseases associated with blood vessels disorder. FIR also used to regulate temperature in incubator for infant. This study aims at exploring correlation pattern between FIR and temperature, producing a biological simulator model from a non-biological material for further research can be initiated. Differentiation factors between biological and non-biological material that exposed to FIR also could be determined. A radiant far-infrared type T -FSR was placed 20 cm above the objects (umbilicus and gel). Then both surface and inside temperature of the objects measured continuously using Thermistor series D-S06 and series D-RB2. Room humidity maintained at constant levels (60%). This study found a significant correlation between FIR and temperature increasing both on the umbilicus and on the gel. Influence of FIR intensity on temperature can be formulated into the formula: T_umb_U1 = 27,6 + 0,00554 FIR and T_umb_U2 = 27,8 + 0,00560 FIR, while on the gel were T_gel_U1 = 24,9 + 0,00430 FIR and T_gel_U2 = 25,0 + 0,00428 FIR.